2022
DOI: 10.1039/d1fo02808a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different moisture contents on the structural and functional properties of cellulose with cell wall components in different citrus fibres

Abstract: This research used a multimethod approach to analyse the influence of different moisture levels (low, medium and high) on structural and functional properties of cellulose with cell wall materials such...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…Stem vascular bundle cells, ducts, and fiber cells gradually lose their protoplasm during development, leaving only the cell wall to provide mechanical support. Cell walls are mainly composed of cellulose, hemicellulose, pectin, and lignin (Kristensen et al., 2022). Recent studies have shown that S‐acylation modifications are required for cellulose synthase complex (CSC) localization to the cell membrane (Purushotham et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Stem vascular bundle cells, ducts, and fiber cells gradually lose their protoplasm during development, leaving only the cell wall to provide mechanical support. Cell walls are mainly composed of cellulose, hemicellulose, pectin, and lignin (Kristensen et al., 2022). Recent studies have shown that S‐acylation modifications are required for cellulose synthase complex (CSC) localization to the cell membrane (Purushotham et al., 2020).…”
Section: Introductionmentioning
confidence: 99%